Process modeling: technological innovation to control the risk for perioperative positioning injury - Ana Luzia Rodrigues; Fernanda Broering Gomes Torres; Eduardo Alves Portela Santos; Marcia Regina Cubas (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to report the construction of a process model to support the decision making of operating room nurses to control the risk for perioperative positioning injury. Methods: experience report on a process model that helps nurses with decision making regarding clients at risk for perioperative positioning injury. By following the steps, it was possible to identify intrinsic and extrinsic variables of the literature and of the workflows of teams involved in the positioning of the client for surgery. The Business Process Model and Notation, the Bizagi Modeler software and terms from the International Classification for Nursing Practice were used in the model. Results: the experience allowed the observation of the knowledge integration between different areas, which enabled the process modeling and its validation. Conclusions: process modeling is an innovative option for the development of support systems for clinical nursing decisions.